Pentamidine Inhibits Ovarian Cancer Cell Proliferation and Migration by Maintaining Stability of PTEN in vitro - Wu Y; Zhang Z; Kou Z (Dove Medical Press, 2021)
Yi Wu,1 Zhong Zhang,2 Zuqiang Kou3 1Department of Pathogenic Biology, Shenyang Medical College, Shenyang City, Liaoning Province, 110004, People's Republic of China; 2Department of Pathology, Shenyang Medical College, Shenyang City, Liaoning Province, 110004, People's Republic of China; 3Department of Logistics, Shenyang Ligong University, Shenyang City, Liaoning Province, 110004, People's Republic of ChinaCorrespondence: Yi WuDepartment of Pathogenic Biology, Shenyang Medical College, Shenyang City, Liaoning Province, 110004, People's Republic of ChinaTel/Fax +86-24-62215720Email 79685970@qq.comPurpose: Pentamidine is an anti-protozoal cationic aromatic diamidine drug and has been reported to exhibit anticancer properties. We aimed to identify the effect of pentamidine on proliferation and migration of human ovarian cancer (OC) cell lines and the related mechanisms.Methods: HO8910 and Caov3 ovarian cancer cells were treated with pentamidine. MTS and colony formation assays were used to detect the proliferation ability of cells. The migration of cells was detected using wound healing and transwell assays. The protein levels of PTEN, phosphorylated Akt, Akt, N-cadherin, E-cadherin and snail were detected by Western blotting. Immunoprecipitation and Western blotting were used to detect ubiquitination levels of PTEN.Results: Our findings revealed that pentamidine inhibited both proliferation and migration of OC cells. Further investigation found that pentamidine increased the protein expression of PTEN and reduced phosphorylation levels of AKT in OC cells. Pentamidine treatment modulated PTEN stability through the ubiquitin/proteasome pathway. In addition, pentamidine inhibited the expression of N-cadherin and snail, and increased E-cadherin expression in a dose-dependent manner.Conclusion: Pentamidine is involved in the maintenance of PTEN protein stability and suppresses proliferation and migration of OC cells.Keywords: pentamidine, ovarian cancer, PTEN